Fighting Words : Working-Class Formation, Collective Action, and Discourse in Early Nineteenth-Century England - Steinberg, Marc W. (Marc William), 1956- (Book collections on Project MUSE., 1999)
"A key component of social life, discourse mediates the processes of class formation and social conflict. Drawing on dialogic theory and building on the work of E.P. Thompson, Mare W. Steinberg argues for the importance of incorporating discursive analysis into the historical reconstruction of class experience. Amending models of collective action, he offers new insights on how discourse shapes the dynamics of popular protest. To support his thesis, he presents studies of two English trade groups fighting economic subordination and degradation in the 1820s; cotton spinners from Lancashire factory towns and London silk weavers."--Jacket